Towards a contextual theology of conviviality: Tutu, Bonhoeffer and living musical metaphors - A.M. Coates; J. Kunnuji (Acta Theologica)
Both Tutu and Bonhoeffer embraced conviviality as an attribute of Christian life, not only as theory, but also in practice. Both also drew from lived experience in an effort to articulate their respective theologies of conviviality. We discuss the experience of music and musical metaphors as a lens through which to explore this relationship between lived experience and an explicit theology of conviviality. Bonhoeffer’s metaphor of the “polyphony of life” is a product of his milieu and does not fully capture the conviviality implicit in his Christology (being-for-others). We argue that African manifestations of conviviality such as ubuntu and gbenopo, when understood as lived realities rather than isolated abstract concepts, make an important contribution to theological discourse, in general. In this case in particular, utilising ethnomusicology to attend to the polyrhythm in Ogu music enriches our understanding of what it means to be-for-others.